1971
DOI: 10.1037/h0031163
|View full text |Cite
|
Sign up to set email alerts
|

Primary auditory stream segregation and perception of order in rapid sequences of tones.

Abstract: A recent finding of the inability of listeners to judge the order of three or four nonspeech sounds presented in a repetitive cycle is explained by the concept of stream segregation. Two experiments showed that at high presention rates of a short cycle of six tones (three high and three low), 5s invariably segregated the tone sequences into streams based on frequency and could perceive only those patterns relating elements of the same subjective stream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
472
1
1

Year Published

1977
1977
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(499 citation statements)
references
References 7 publications
25
472
1
1
Order By: Relevance
“…We see the present phenomena as lying on a continuum with those involving perceptual splitting of rapid pitch sequences alternating between widely separated pitch regions. (Bregman & Campbell, 1971;Dowling, 1973). However, this is not the only possible way of viewing these phenomena.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We see the present phenomena as lying on a continuum with those involving perceptual splitting of rapid pitch sequences alternating between widely separated pitch regions. (Bregman & Campbell, 1971;Dowling, 1973). However, this is not the only possible way of viewing these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…And people are generally very precise in reproducing well-known musical scale intervals within the octave (Attneave & Olson, 1971). On the other hand, Bregman and Campbell (1971) showed that recognition of identity between three-note melodies with very wide pitch skips in them is worse than for melodies with relatively narrow skips. The processing of melodic information seems particularly difficult when wide changes of pitch are involved.…”
mentioning
confidence: 99%
“…Similarly, Pressnitzer & Hupé [34] have shown that although ambiguous auditory streaming [35,36] and moving visual plaids [37] follow similar temporal courses, they alternate independently.…”
Section: Bindingmentioning
confidence: 99%
“…For example, audition researcher Bregman (1990) claims that hearing involves the parsing of auditory scenes into distinct auditory streams-which can be understood as a kind of boundary allocation-and studies show that listeners are unable to pay attention to more than one sound stream at a time, which is also indicative of figure-ground segregation. One such study by Bregman and Campbell (1971) found that perceivers were unable to judge the order of sounds presented in a repetitive cycle where these sounds were experienced as two distinct streams. Participants were presented with three high-pitched sounds (ABC) and three lowpitched sounds (123) in the order A-1-B-2-C-3.…”
Section: Figure-ground Segregationmentioning
confidence: 99%